Axial Elongation of Mononuclear Lanthanide Metallocenophanes: Magnetic Properties of Dysprosium‐ and Terbium‐[1]Ruthenocenophane Complexes. Issue 32 (27th May 2020) - Risica, Gabrielle M.; Vieru, Veacheslav; Wilkins, Branford O.; Latendresse, Trevor P.; Reibenspies, Joseph H.; Bhuvanesh, Nattamai S.; Wylie, Gregory P.; Chibotaru, Liviu F.; Nippe, Michael
Abstract: We report the first f‐block‐ruthenocenophane complexes 1 (Dy) and 2 (Tb) and provide a comparative discussion of their magnetic structure with respect to earlier reported ferrocenophane analogues. While axial elongation of the rare trigonal‐prismatic geometry stabilizes the magnetic ground state in the case of Dy 3+ and results in a larger barrier to magnetization reversal ( U ), a decrease in U is observed for the case of Tb 3+ . Abstract : The first f‐block ‐[1]ruthenocenophane complexes are reported and their dynamic magnetic properties are compared to those of their ferrocenophane congeners, which can be considered axially compressed analogues. Axial elongation affects the barrier of magnetization reversal for Dy 3+ (increase) and Tb 3+ (decrease) differently. These opposing trends are rationalized by ab initio computations.